The first modern Japanese : the life of Ishikawa Takuboku - Keene, Donald (Asia perspectives., 2016)
"Thousands of books and monographs have been devoted to the poet and critic Ishikawa Takuboku (1886-1912). Although he died at the age of twenty-six and wrote many of his best-known poems in the space of a few years, his name is familiar to every literate Japanese. His early death added to the sad romance of the unhappy poet, but there has been no satisfactory biography of his life or career, even in Japanese, and only a small part of his writings have been translated. His mature poetry was based on the work of no predecessor, and he left no disciples. He stands unique. Takuboku's most popular poems, especially those with a humorous overlay, are well read and memorized, but his diaries and letters, though less familiar, contain rich and vivid glimpses of the poet's thoughts and experiences. They reflect the outlook of an unconstrained man who at times behaved in a startling or even shocking manner. Despite his misdemeanors, Takuboku is regarded as a national poet, all but a saint to his admirers, especially in the regions of Japan where he lived. His refusal to conform to the Japan of the time drove him in striking directions and ranked him as the first poet of the new Japan"--Provided by publisher.